Lithium Ion Capacitors in Organic Electrolyte System: Scientific Problems, Material Development, and Key Technologies. Issue 26 (28th August 2018) - Han, Pengxian; Xu, Gaojie; Han, Xiaoqi; Zhao, Jingwen; Zhou, Xinhong; Cui, Guanglei
Abstract: Lithium ion capacitors (LICs), which are hybrid electrochemical energy storage devices combining the intercalation/deintercalation mechanism of a lithium‐ion battery (LIB) electrode with the adsorption/desorption mechanism of an electric double‐layer capacitor (EDLC) electrode, have been extensively investigated during the past few years by virtue of their high energy density, rapid power output, and excellent cycleability. In this review, the LICs are defined as the devices with an electrochemical intercalation electrode and a capacitive electrode in organic electrolytes. Both electrodes can serve as anode or cathode. Throughout the history of LICs, tremendous efforts have been devoted to design suitable electrode materials or develop novel type LIC systems. However, one of the key challenges encountered by LICs is how to balance the sluggish kinetics of intercalation electrodes with high specific capacity against the high power characteristics of capacitive electrode with low specific capacitance. Herein, the developments and the latest advances of LIC in material design strategies and key techniques according to the basic scientific problems are summarized. Perspectives for further development of LICs toward practical applications are also proposed. Abstract : Lithium ion capacitors have been extensively investigated due to their high energy density, rapid power output, and excellent cycling durability. The mismatching between the sluggish kinetics of intercalation electrodes and the high power characteristics of capacitive electrodes is one of their great challenges. The development of advanced materials and novel devices becomes more and more important.